Upaya Peningkatan Aktivitas Dan Hasil Belajar Siswa Melalui Model Project Based Learning Berbasis IT - Arini Badri (Jurnal Guru Dikmen dan Diksus, 2023)
This research aimed to improve students’ activities and learning achievement through the Project Based Learning (PjBL) model that is integrated with IT based learning media on Virtual Local Area Network (VLAN) subject. The IT based learning media used are google workspace for education, AnyDesk and Canva Applications which are used to create online and collaborative projects. The sample of the study was 36 students of class XI TKJ SMKN 4 Palembang. The research method was classroom action research which was divided into several stages of planning, action, observation and reflection which were carried out in three cycles. The result showed that students learning activities in the first cycle were 70.31%, the second cycle was 74.58% and in the third cycle increased to 85.06% while for the learning achievement in the pre cycle with an average value of 52.44, in the first cycle after being given an action in the form of an IT based PjBL model amount of 70.31, the second cycle of 74,58 and in the third cycle it increased 85.06. The finding showed that using the PjBL learning model that is integrated with IT based learning media could significantly improve students’ activities and learning achievement.